UHPLC-Q-Orbitrap /MS2 identification of (+)-Catechin oxidation reaction dimeric products in red wines and grape seed extracts. (15th July 2022) - Deshaies, Stacy; Sommerer, Nicolas; Garcia, François; Mouls, Laetitia; Saucier, Cédric
Highlights: B-type procyanidin dimer and new catechin dimeric oxidation products were analyzed. Depending on dimer type (B, COC or CC), specific mass fragments were obtained. 3 oxidation markers were identified in seeds with an increasing trend with ripening. 3 oxidation markers were identified in wines with a decreasing trend with ageing. Abstract: B-type procyanidin dimers and (+)-catechin dimeric oxidation products were analyzed in grape seed extracts and red wines (UHPLC-Q-Orbitrap MS). The different dimers had different fragmentation patterns according to their interflavan linkage position. Oxidation dimeric compounds had a specific fragment ion at m / z 393, missing for B-Type dimers fragmentations. A fragment ion at m / z 291 occurred and was specific for oxidation dimeric compounds with a COC linkage. Higher level oxidation products had abundant specific fragments: m / z 425, 397 and 245. These fragmentations were useful to identify them in complex samples such as grape seed extracts and wines. Three grape varieties and three ripening stages were selected and the corresponding seed extracts were obtained. The analyses revealed an increasing trend for the oxidation markers during grape ripening. The analysis of Syrah wines (2018, 2014, 2010) showed a decreasing trend of these molecules during wine ageing which might be due to further oxidation.